Antioxidant andAntimicrobial Properties of Leaves of Lyonia ovalifolia Wallich - Acharya, Santosh Raman (International Journal of Pharmaceutical & Biological Archive, 2015)
Antioxidant andAntimicrobial Properties of Leaves of Lyonia ovalifolia Wallich